Identification of oxygen-19 during in vivo neutron activation analysis of water phantoms. (26th October 2015) - Tahir, Syed N A; Chettle, David R
Abstract: Hand bone equivalent phantoms (250 ml) carrying selenium in various amounts were irradiated and counted for in vivo neutron activation analysis (IVNAA) by employing a 4 π NaI(TI) based detection system. During the analysis of counting data, a feature at a higher energy than the gamma ray peak from 77m Se (0.162 MeV) was observed at 0.197 MeV. Further investigations were made by preparing water phantoms containing only de-ionized water in 250 ml and 1034 ml quantities. Neutrons were produced by the 7 Li( p, n ) 7 Be reaction using the high beam current Tandetron accelerator. Phantoms were irradiated at a fixed proton energy of 2.3 MeV and proton currents of 400 μ A and 550 μ A for 30 s and 22 s respectively. The counting data saved using the 4 π NaI(TI) detection system for 10 s intervals in anticoincidence, coincidence and singles modes of detection were analyzed. Areas under gamma peaks at energies 0.197 MeV and 1.357 MeV were computed and half-lives from the number of counts for the two peaks were established. It was concluded that during neutron activation of water phantoms, oxygen-18 is activated, producing short-lived radioactive 19 O having T 1/2   =  26.9 s. Induced activity from 19 O may contribute spectral interference in the gamma ray spectrum. This effect may need to be taken into account by researchers while carrying out IVNAA of biological subjects.